(untitled) (Annual of Sofia University St. Kliment Ohridski. Faculty of Mathematics and Informatics, 2004)
We introduce and study the notion of joint spectrum of finitely many abstract structures. A characterization of the lower bounds of the elements of the joint spectrum is obtained.